Finasteride for androgenetic alopecia is not associated with sexual dysfunction: a survey‐based, single‐centre, controlled study. (15th April 2019) - Haber, R.S.; Gupta, A.K.; Epstein, E.; Carviel, J.L.; Foley, K.A.
Abstract: Background: The occurrence of sexual dysfunction side‐effects associated with finasteride use in men with androgenetic alopecia (AGA) is thought to be less prevalent than is publicized. There is a need to investigate sexual dysfunction among finasteride users with population‐based controls. Objective: To evaluate the presence of sexual dysfunction in men using finasteride or not using finasteride. Method: Adult men visiting a dermatologist's office for any reason were asked to complete a survey including a modified version of the Arizona Sexual Experience Scale (ASEX) to assess the presence of sexual dysfunction with and without finasteride use. Results: Data from 762 men aged 18–82 were collected: 663 finasteride users and 99 non‐finasteride users. There were no significant differences between finasteride users and non‐user controls in reporting sexual dysfunction using the ASEX. Regression analysis indicated that self‐reporting libido loss and reduced sexual performance, not finasteride use, predict a higher ASEX score. Conclusion: The use of finasteride does not result in sexual dysfunction in men with AGA. These data are consistent with other large survey‐based controlled studies.